An adeno-associated virus gene therapy strategy for anti-obesity treatment by nanocarrier-based delivery systems - Li Li; Wang Wang; Rong Li; Jiayue Guo; Xulin Hu; Yu Pan; Taoyuan Zhang; Sensen Chi; Zili Gu; Gaohui Zhu; Qi Liu; Shuai Tan (Journal of Nanobiotechnology)
Abstract Gut microbiota is increasingly recognized for its profound influence on host metabolism. However, the mechanisms underlying the distinct metabolic phenotype observed in germ-free (GF) mice are not fully understood. Here, the serum levels of metabolic hormones glucagon-like peptide-1 (GLP-1) and peptide YY (PYY) were shown with significant elevation in GF than the conventionally-raised (CONV-R) mice. Single-cell transcriptome analysis revealed that Secretogranin II (Scg2), with a known function in secretion control, was exclusively expressed in enteroendocrine cells (EECs). Scg2 transcript levels were significantly up-regulated in GF mice, positively correlated with enhanced GLP-1 and peptide PYY secretion. To examine the functional significance of Scg2 in hormone regulation, cross-linked nanoparticles capable of long-term adhesion to intestinal epithelium were designed, with AAV adsorbed within the cross-linked structure. This innovative design enhances its stability and retention in vivo, providing a robust platform for continuous and efficient gene delivery. We evidenced that over-expression of Scg2 via AAV-loaded nanocarriers in the colons of mice on high-fat diet or with the ob/ob genotype not only enhanced the secretion of GLP-1 and PYY but also mitigated weight gain in these mice by reducing their appetite. A multi-omics analysis reveals that Scg2 overexpression in the colon decreased hypothalamic inflammation and activated tryptophan metabolic pathways. Collectively, our findings suggest a potential therapeutic approach for treating metabolic disorders by enhancing Scg2 expression in colonic EECs. Graphical Abstract